Highly oriented 1-D ZnO nanorod arrays on zinc foil: Direct growth from substrate, optical properties and photocatalytic activities - Wang, Y.; Li, Xin Yong; Lu, G.; Quan, X.; Chen, G. (American Chemical Society, 2008)
Highly oriented and large-scale ZnO nanorod arrays have been successfully synthesized on zinc foil by a simple, low-temperature, solution-phase approach. In this approach, zinc foil was used not only as a substrate but also as a zinc-ion source for the direct growth of ZnO nanorod arrays. X-ray diffraction (XRD) analysis, high-resolution TEM (HRTEM) images, and selected-area electron diffraction (SAED) patterns indicated that the structure of the ZnO nanorod arrays on the zinc foil substrate was single-crystalline and grown in the [0001] direction with a wurtzite structure. The optical properties of the ZnO nanorod arrays were characterized by UV-vis diffuse reflectance, Raman, and photoluminescence spectroscopies. The photocatalytic activity of the ZnO nanorod arrays was tested by degradation of 4-chlorophenol (4-CP) under UV light irradiation compared to that of a ZnO nanorod film grown on a Ti substrate, indicating that the as-synthesized ZnO nanorod arrays exhibit excellent photocatalytic activity. © 2008 American Chemical Society.